2019
DOI: 10.1186/s12906-019-2772-5
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacology based approach to investigate the in-vivo therapeutic efficacy of Albizia lebbeck (L.) in experimental model of Parkinson’s disease

Abstract: BackgroundParkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by loss of dopaminergic neurons in substantia nigra pars compacta and clinically manifested mainly with motor dysfunctions. Plants are rich source of medicinally important bioactive compounds and inhabitants of underdeveloped countries used plants for treatment of various ailments. Albizia lebbeck has been reported to possess antioxidant and neuroprotective properties that suggest the evaluation of its traditional ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…(Trevitt et al., 2009; Maj et al., 1990; Juszkiewicz et al., 1994; Juszkiewicz et al., 1995; Mandhane et al., 1997; Konieczny et al., 1999; Jagtap & Inamdar, 2001; Ossowska et al., 2001; Breysse et al., 2002; Moo‐Puc et al., 2003; Ossowska et al., 2003; Rukoyatkina et al., 2003; Wardas et al., 2003; Tanganelli et al., 2004; Ossowska et al., 2005; Zazpe et al., 2006; Lopez et al., 2007; Sibille et al., 2007; Ahemad et al., 2009; Beurrier et al., 2009; Góngora‐Alfaro et al., 2009; Konieczny et al., 2009; Ardashov et al., 2011; Joshi et al., 2011; Trevizol et al., 2011; Lopez et al., 2012; Shyamjith et al., 2012; Goudet et al., 2012; Acuña‐Lizama et al., 2013; Konieczny & Lenda, 2013; Atack et al., 2014; Ittiyavira & Ruby, 2014; Azam, et al., 2009; Zheng et al., 2014; Gmiro et al., 2015; Maurice et al., 2015; Nade et al., 2015; Bhangale & Acharya, 2016; Dhingra & Gahalain, 2016; Basu et al., 2017; Chitra et al., 2017; Gupta et al., 2017; Kumari et al., 2017; Kronbauer et al., 2017; Tian et al., 2017; Yang et al., 2016; Engelhardt et al., 2018; Slee et al., 2008; Saleem et al., 2019; Kabra et al., 2020; Łażewska et al., 2020; Chiu et al., 1981; Schmidt & Bubser, 1989; Schmidt et al., 1991; Kretschmer, 1994; Kretschmer et al.,…”
Section: Resultsmentioning
confidence: 99%
“…(Trevitt et al., 2009; Maj et al., 1990; Juszkiewicz et al., 1994; Juszkiewicz et al., 1995; Mandhane et al., 1997; Konieczny et al., 1999; Jagtap & Inamdar, 2001; Ossowska et al., 2001; Breysse et al., 2002; Moo‐Puc et al., 2003; Ossowska et al., 2003; Rukoyatkina et al., 2003; Wardas et al., 2003; Tanganelli et al., 2004; Ossowska et al., 2005; Zazpe et al., 2006; Lopez et al., 2007; Sibille et al., 2007; Ahemad et al., 2009; Beurrier et al., 2009; Góngora‐Alfaro et al., 2009; Konieczny et al., 2009; Ardashov et al., 2011; Joshi et al., 2011; Trevizol et al., 2011; Lopez et al., 2012; Shyamjith et al., 2012; Goudet et al., 2012; Acuña‐Lizama et al., 2013; Konieczny & Lenda, 2013; Atack et al., 2014; Ittiyavira & Ruby, 2014; Azam, et al., 2009; Zheng et al., 2014; Gmiro et al., 2015; Maurice et al., 2015; Nade et al., 2015; Bhangale & Acharya, 2016; Dhingra & Gahalain, 2016; Basu et al., 2017; Chitra et al., 2017; Gupta et al., 2017; Kumari et al., 2017; Kronbauer et al., 2017; Tian et al., 2017; Yang et al., 2016; Engelhardt et al., 2018; Slee et al., 2008; Saleem et al., 2019; Kabra et al., 2020; Łażewska et al., 2020; Chiu et al., 1981; Schmidt & Bubser, 1989; Schmidt et al., 1991; Kretschmer, 1994; Kretschmer et al.,…”
Section: Resultsmentioning
confidence: 99%
“…Catalepsy is the inability of animals such as rodents to correct externally imposed position or posture. The previously elucidated method 41 was followed for the determination of catatonia induced by haloperidol (1 mg/kg i.p.). Cataleptic behavior was observed for 30 to 120 min after the administration of haloperidol by the standard bar test (with 3 and 9 cm elevated bars).…”
Section: Methodsmentioning
confidence: 99%
“…The anti-Parkinson activity was evaluated by performing behavioral and biochemical oxidative stress assay in Wistar albino rats. It was observed that the plant extract can be able to ameliorate motor function and prevent biochemical damage in brain cells [ 12 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…It is a deciduous tree that is mostly found in the garden or along the roadside and grows from sea level to 1500 m elevation, attaining height up to 18 m. A. lebbeck contains numerous phytochemicals related to alkaloids, anthraquinones, essential oils, flavonoids, glycosides, phenolics, phytosterol, saponins, steroids, and triterpenoids [ 9 13 ]. According to various pharmacological studies, this species exhibited excellent antinociceptive, anti-inflammatory [ 11 ], anticancer [ 9 ], antimalarial [ 14 ], antiallergic [ 15 ], antihyperglycemic [ 16 ], antidiabetic [ 17 , 18 ], wound healing [ 19 ], nootropic [ 20 ], and neuroprotective activities such as anti-Parkinson's and anti-Alzheimer activities [ 12 , 21 ]. Furthermore, zinc oxide nanoparticles synthesized from Albizia lebbeck stem bark extract caused concentration-dependent organoprotective effect by changing mean body weight, alanine aminotransferase, serum alkaline phosphatase, urea, creatinine, bilirubin, protein, globulin, albumin, total cholesterol, triacylglycerol, and low- and high-density lipoprotein [ 22 ].…”
Section: Introductionmentioning
confidence: 99%